The Effect of Plyometric Hurdle Training on the Vertical Jump of Volleyball Extracurricular Students - Lukas Adi Wira Mohamad Zain; Fajar Syamsudin (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Vertical jump ability is one of the key components of volleyball, especially for executing successful smashes and blocks. Based on observations at SMP Negeri 1 Jambu, the vertical jump ability of students in the volleyball extracurricular program is still not optimal, and the training provided has not specifically focused on improving lower-body explosive power. This study aimed to determine the effect of plyometric hurdle jump training on the vertical jump ability of students in the volleyball extracurricular program at SMP Negeri 1 Jambu. This study employed an experimental method with a one-group pretest-posttest design. The sample consisted of 13 students selected through purposive sampling. The research instrument was a vertical jump test. The plyometric hurdle jump training program was conducted over 12 sessions, three times a week. Data were analyzed using a normality test and a paired-sample t-test. The results showed that the average vertical jump increased from 52.85 cm in the pretest to 59.31 cm in the posttest, an increase of 6.46 cm. The statistical analysis yielded a significance value of 0.000 (p < 0.05). Therefore, plyometric hurdle jump training significantly improved the vertical jump ability of students in the volleyball extracurricular program at SMP Negeri 1 Jambu.